(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The aim of the research is to determine the role of organizational culture in the construction of the capabilities to prepare for crisis management , in order to achieve this aim, the researchers had managed through the theoretical thinking and related studies to a supposed diagram showing the relation between the variable that had been studied, the research had depended on the study of organizational culture as an independent variable divided into six dimensions ( trust , collective culture , a shared vision , language and common stories , management practices , and cultural norms )in addition to other six dimensions represent the considerable variable in the construction to prepare for crisis management which are( strategic movements , technical and structural movements , procedures of recognizing and auditing , speed of response decision , communications, and mobilization of resources ) the sample consisted of (30) managers from the national Center for administrative development and information technology , The research reached several results, represented by the contribution of organizational culture in building the capabilities of preparedness for crisis management, through the results of the correlation relationship. The most important recommendations were the need for the National Center for Administrative Development and Information Technology to create a climate of trust and benefit from stories of leadership and success in building preparedness capabilities to manage the crisis